IOT IMPLEMENTATION FOR CALCULATING POWER CONSUMPTION BASED ON ANDROID - Agung Kridoyono; Mochamad Sidqon; Anton Breva Yunanda (Jurnal Simantec, 2022)
Electrical power consumption monitoring, mainly at business properties in urban areas that have one line power supply distribution at many area rent, had the problem of the bill electric consumption on the tenant. The places like dormitories, food court, futsal field, pets day care etc. had problems, where the node had more electrical consumption operationally, so we implemented IoT monitoring and control at  electrical device and electrical consumption report. The method to implement this system is using IoT protocol communication and firebase cloud data as a third party database application that is accessed by an android mobile phone. The systems of our research is infrastructure IoT mobile communication that can be controlled and adjusted by firebase cloud and can activate the device by MCU microcontroller ESP wifi that Based to monitor and record activity that had controlled by mobile phone. All data activity has to be processed and saved to the firebase data cloud, so the system depends on internet communication and an active firebase server. So the result of our research is to report activity and bill of electrical consumption every node that had rented.